A thermal-coupled/gas-coupled hybrid high-frequency pulse tube cryocooler attaining the liquid-helium temperature. Issue 1 (1st May 2022) - Yang, Biao; Gao, Zhaozhao; Xi, Xiaotong; Chen, Liubiao; Wang, Junjie
Abstract: High-frequency pulse tube cryocooler (HPTC) has become an attractive method for space cooling in the liquid-helium temperature range, due to its advantages of potential high efficiency, no moving parts at the cold end, small size, and light weight. However, key problems such as large regenerator losses and insufficient phase-shifting ability challenge it to obtain the liquid-helium temperature. A thermal-coupled/gas-coupled hybrid refrigeration process of HPTC has been designed to obtain the liquid-helium temperature. One HPTC working in the liquid-nitrogen temperature range is used as a pre-cooling stage, and another two-stage gas-coupled structure is employed to obtain liquid-helium temperature. The simulation results show that the lowest no-load temperature is 3.6 K and a cooling power of 84 mW can be provided at 6 K with a total input PV power of 128 W and 10.9 W/77 K pre-cooling power when Helium-4 is chosen as the working gas. An experimental prototype was designed, built, and tested. The simulation and experiment results will be introduced in detail in this paper.